If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + 14x = 2x + -1 Reorder the terms: -13 + 14x = -1 + 2x Solving -13 + 14x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -13 + 14x + -2x = -1 + 2x + -2x Combine like terms: 14x + -2x = 12x -13 + 12x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 -13 + 12x = -1 + 0 -13 + 12x = -1 Add '13' to each side of the equation. -13 + 13 + 12x = -1 + 13 Combine like terms: -13 + 13 = 0 0 + 12x = -1 + 13 12x = -1 + 13 Combine like terms: -1 + 13 = 12 12x = 12 Divide each side by '12'. x = 1 Simplifying x = 1
| -11(-11x+-3)+-9(4x+8)=-39 | | 2w+18=-w-5 | | 1/3m=1 | | 4c-y=2 | | 50-4x=6x+10 | | 16x+5y=900 | | 5x+8x-2x-5=50 | | 8(p+1)-7=15p-4 | | x/5x20=12 | | 17x+4y=5 | | 5(w+6)-7w=12 | | X/5x20= | | x=0.3x+0.3 | | 2m-6/5=-2 | | 5a^2-20a= | | 100+10m=155m | | -d/2=252-491-51508 | | x=72x^2 | | 2x-19=3x+7 | | Z/5-6=2 | | 11X+12=4X+24 | | 2(12x+11)=12(2x+12) | | 2(3x-5)+2x= | | 3/5x/74/5 | | -9r=-9 | | 5x+20+4x+11=180 | | 5x^2+46x+9=0 | | 180+4x=180 | | 24+5x=3+5(x+5) | | x+12=2(x+6)+4 | | x=-8y-7 | | -10+3b=5b-26 |